1983
DOI: 10.1161/01.hyp.5.5_pt_2.iii120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antihypertensive therapy on serum lipoproteins.

Abstract: Several drugs used for standard antihypertensive therapy may also interact with the lipoprotein metabolism. The following has been observed after 1 to 12 months of treatment. Various thiazide-type diuretics may significantly increase the potentially atherogenic serum low-density-lipoprotein cholesterol (LDL-C) and/or very-LDL-C-fractions, while the antiatherogenic high-density-lipoprotein cholesterol (HDL-C) is largely unchanged. Certain loop-diuretics also increase the LDL-C/HDL-C ratio and both types of diur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…These results are consistent with the Lipid Research Clinics' observation of a lower HDL cholesterol level and a higher TG level in the small group of subjects receiving propranolol in comparison with matched controls from the same study population. 31 Our finding of similar levels of TC and LDL cholesterol in treated and untreated hypertensive subjects suggests that: 1) diuretics were most often prescribed in conjunction with beta-blockers, which prevent the increase in TC and LDL cholesterol normally associated with diuretic therapy; 16 or 2) the effects of diuretic monotherapy on TC and LDL cholesterol are not of sufficient magnitude or duration to significantly affect population lipid or lipoprotein levels.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with the Lipid Research Clinics' observation of a lower HDL cholesterol level and a higher TG level in the small group of subjects receiving propranolol in comparison with matched controls from the same study population. 31 Our finding of similar levels of TC and LDL cholesterol in treated and untreated hypertensive subjects suggests that: 1) diuretics were most often prescribed in conjunction with beta-blockers, which prevent the increase in TC and LDL cholesterol normally associated with diuretic therapy; 16 or 2) the effects of diuretic monotherapy on TC and LDL cholesterol are not of sufficient magnitude or duration to significantly affect population lipid or lipoprotein levels.…”
Section: Discussionmentioning
confidence: 89%
“…10 " 15 When beta-blockers and diuretics are given concurrently, HDL cholesterol is decreased and TG is increased, but there is no increase in total cholesterol or LDL cholesterol. 16 Decreases in HDL cholesterol have also been reported 1718 after treatment with methyldopa. The changes in plasma lipid and lipoprotein levels associated with antihypertensive treatment have been shown 17 to significantly offset the reduction in the calculated risk of coronary artery disease (CAD) that results from blood pressure reduction.…”
mentioning
confidence: 96%
“…Also, HDL-C and, whenever measured, HDL's major apoproteins Al and A2 (apo Al and A2) were largely unchanged with thiazides. 12 This documents a frequent occurrence of elevated LDL-C/HDL-C and total C/HDL-C ratios in thiazidetreated men or postmenopausal women. Loop diuretics, such as furosemide, mefruside, and muzolimine, also increased these ratios due to mildly raised total or LDL-C and unchanged or even slightly decreased HDL-C values.…”
mentioning
confidence: 87%
“…8 More recent studies 9 "" focused on impaired lipid metabolism due to long-term therapy with sulfonamide diuretics. Weidmann et al 12 showed that hydrochlorothiazides and chlorthalidone increase plasma triglycerides and total cholesterol in mildly hypertensive patients. Other investigations also demonstrated a tendency to increased triglyceride and/or total cholesterol levels in patients treated with thiazide diuretics.""…”
Section: (Hypertension 7 [Suppl It]: Ii-170-h-174 1985) Abstract • mentioning
confidence: 99%
“…Whether or not elevation of serum LDL cholesterol levels during treatment with chlorthalidone or hydrochlorothiazide 13 or elevation of beta-lipoprotein fraction during furosemide therapy 12 will persist during long-term treatment and modify the coronary risk is presently unknown.…”
Section: -173mentioning
confidence: 99%